EFEKTIVITAS PELAKSANAAN PROGRAM PEMBANGUNAN INFRASTRUKTUR PERDESAAN (Studi : Desa Bulude, Kecamatan Kabaruan Kabupaten Kepulauan Talaud, Sulawesi Utara) - RUMPIA, GIFFRIED; KIYAI, BURHANUDDIN; KOLONDAM, HELLY (Sam Ratulangi University, 2019)
This research aims to know the effectiveness of the implementation of Rural Infrastructure development programme in the village Bulude, district Kabaruan Talaud Islands Regency. This research uses qualitative descriptive approach, the author assesses the effectiveness indicators based on data collected through in-depth interview techniques, the study of librarianship, and observations. Against 10 informants directly related to the implementation of the rural development programme in the village of Bulude Sub-district Kabaruan. Through this research is also Bulude Village Government and people could find out if the program has been running effectively?. After the data is collected, either in the process of collecting and after collecting the data, and then in the analysis with the results it was concluded that is the implementation of the programme of infrastructure development in the rural village of Bulude had enough runs well were carried out and completed in a timely manner.Key words: Effectiveness, Rural Infrastructure, development.